2019
DOI: 10.3389/fendo.2019.00709
|View full text |Cite
|
Sign up to set email alerts
|

Orexins as Novel Therapeutic Targets in Inflammatory and Neurodegenerative Diseases

Abstract: Orexins [orexin-A (OXA) and orexin-B (OXB)] are two isoforms of neuropeptides produced by the hypothalamus. The main biological actions of orexins, focused on the central nervous system, are to control the sleep/wake process, appetite and feeding, energy homeostasis, drug addiction, and cognitive processes. These effects are mediated by two G protein-coupled receptor (GPCR) subtypes named OX1R and OX2R. In accordance with the synergic and dynamic relationship between the nervous and immune systems, orexins als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 155 publications
(200 reference statements)
0
60
0
2
Order By: Relevance
“…anti-in ammatory) properties. Studies show that orexins may have therapeutic potential in several pathologies with a single immune component, including multiple sclerosis, Alzheimer's disease, obesity, septic shock, and cancer [41]. We suggest more investigations into dietary-dependent neuropathy in MS patients and more in-depth examinations of the role of BMI in MS patients.…”
Section: Discussionmentioning
confidence: 91%
“…anti-in ammatory) properties. Studies show that orexins may have therapeutic potential in several pathologies with a single immune component, including multiple sclerosis, Alzheimer's disease, obesity, septic shock, and cancer [41]. We suggest more investigations into dietary-dependent neuropathy in MS patients and more in-depth examinations of the role of BMI in MS patients.…”
Section: Discussionmentioning
confidence: 91%
“…As a general remark, the effect of OXB has been less investigated, possibly due to its considerably lesser affinity for OX2. However, Sokołowska et al [ 43 ] demonstrated a potent antioxidant effect of OXB in primary neuronal rat culture and a therapeutic use has also been hypothesized [ 44 ]. It should be noted that our findings are of particular interest, since redox status regulation generally plays a central role in follicular function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, OXA has an immunoregulatory and neuroprotective action, inhibiting apoptosis and reducing inflammation. Moreover, OXA seems to have an action on microglia, with promising implications not only for tumors and inflammatory diseases but also for neurodegenerative diseases, although data on these are still scarce [ 157 ]. The orexin receptor antagonist suvorexant might be useful for the prevention and treatment of AD because of its neuroprotective effect, with reduction of β-amyloid plaques and improvement of synaptic plasticity [ 158 ].…”
Section: Orexin Cancer and Neurodegenerative Diseasesmentioning
confidence: 99%